Deletion of Alzheimer's disease‐associated CD33 results in an inflammatory human microglia phenotype. Issue 6 (4th February 2021) - Wißfeld, Jannis; Nozaki, Ichiro; Mathews, Mona; Raschka, Tamara; Ebeling, Christian; Hornung, Veit; Brüstle, Oliver; Neumann, Harald
Abstract: Genome‐wide association studies demonstrated that polymorphisms in the CD33/sialic acid‐binding immunoglobulin‐like lectin 3 gene are associated with late‐onset Alzheimer's disease (AD). CD33 is expressed on myeloid immune cells and mediates inhibitory signaling through protein tyrosine phosphatases, but the exact function of CD33 in microglia is still unknown. Here, we analyzed CD33 knockout human THP1 macrophages and human induced pluripotent stem cell‐derived microglia for immunoreceptor tyrosine‐based activation motif pathway activation, cytokine transcription, phagocytosis, and phagocytosis‐associated oxidative burst. Transcriptome analysis of the macrophage lines showed that knockout of CD33 as well as knockdown of the CD33 signaling‐associated protein tyrosine phosphatase, nonreceptor type 6 ( PTPN6) led to constitutive activation of inflammation‐related pathways. Moreover, deletion of CD33 or expression of Exon 2‐deleted CD33 (CD33 ΔE2 /CD33m) led to increased phosphorylation of the kinases spleen tyrosine kinase (SYK) and extracellular signal‐regulated kinase 1 and 2 (ERK1 and 2). Transcript analysis by quantitative real‐time polymerase chain reaction confirmed increased levels of interleukin ( IL) 1B, IL8, and IL10 after knockout of CD33 in macrophages and microglia. In addition, upregulation of the gene transcripts of the AD‐associated phosphatase INPP5D was observed after knockout of CD33 . Functional analysis of macrophages and microglia showed that phagocytosis of aggregated amyloid‐β1‐42 and bacterial particles were increased after knockout of CD33 or CD33 ΔE2 expression and knockdown of PTPN6 . Furthermore, the phagocytic oxidative burst during uptake of amyloid‐β1‐42 or bacterial particles was increased after CD33 knockout but not in CD33 ΔE2 ‐expressing microglia. In summary, deletion of CD33 or expression of CD33 ΔE2 in human macrophages and microglia resulted in putative beneficial phagocytosis of amyloid β1‐42, but potentially detrimental oxidative burst and inflammation, which was absent in CD33 ΔE2 ‐expressing microglia. Main points: Ablation of the myeloid receptor CD33 in human macrophages and microglia causes increased activation of the SYK/ERK1/2 signaling axis, phagocytosis, phagocytic oxidative burst and inflammation.